2008
DOI: 10.1265/jjh.63.699
|View full text |Cite
|
Sign up to set email alerts
|

Association between Minamata Disease Status and Activities of Daily Living among Inhabitants in Previously Methylmercury-Polluted Areas

Abstract: Early, Recent, and Not Yet had lower ADL grades than Normal. Moreover, the population with a low ADL grade and health-related anxieties had increased throughout the previously methylmercury-polluted areas. The issue of ill health among populations living in previously methylmercury-polluted areas should be addressed in the wider context of public and community health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Details on sampling methods in the Shiranui Study have been described elsewhere [13]. Briefly, of the approximately 59,000 residents aged 40-79 years of 172 postal code areas across 6 local government regions in the Shiranui Sea area, 105 (1 person per household) per postal code area were randomly sampled.…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…Details on sampling methods in the Shiranui Study have been described elsewhere [13]. Briefly, of the approximately 59,000 residents aged 40-79 years of 172 postal code areas across 6 local government regions in the Shiranui Sea area, 105 (1 person per household) per postal code area were randomly sampled.…”
Section: Study Populationmentioning
confidence: 99%
“…Recent studies have reported that perceived health as compared with residents of non-polluted areas is poor even among residents of the affected area not diagnosed with MD or compensated [12,13]. It has also been reported that many residents of the affected area cannot eliminate worries about their symptoms (even though not typical MD symptoms) that might be related to exposure to methylmercury.…”
Section: Introductionmentioning
confidence: 99%